Effects Of Social Media Marketing, Content Marketing, And Electronic Word Of Mouth On The Customers’ Decision To Use The Bank Aladin Syariah - Erina Eiyanti; Adha, Mufti Alam; Riduwan (Universitas Ahmad Dahlan, 2024)
Introduction to The Problem: This study analyzed the effects of Social Media Marketing, Content Marketing, and Electronic Word of Mouth on the customers' decision to use Bank Aladin Syariah, one of the Islamic Digital banks in Indonesia. Purpose/Objective Study: The research object was Bank Aladin Syariah customers throughout Indonesia. Design/Methodology/Approach: This study used online questionnaires and obtained 100 respondents who were Bank Aladin Syariah's customers using purposive sampling. This study used a quantitative method with multiple linear regression analysis, t-test, f-test, and coefficient of determination test. Findings: The results indicated that, positively and significantly, Social Media Marketing affected the customers' decision to use Bank Aladin Syariah; Content Marketing did not affect the customers' decision to use Bank Aladin Syariah; positively and significantly, the Electronic Word of Mouth affected the customers' decision to use Bank Aladin Syariah. Simultaneously, positively and significantly, Social Media Marketing, Content Marketing, and Electronic Word of Mouth affected the customers' decision to use Bank Aladin Syariah. Paper Type: Research Article